Advances in Tourism Education: A Qualitative Inquiry about Emergency Remote Teaching in Higher Education - FUCHS, Kevin (Journal of Environmental Management and Tourism, 2021)
Online education, in its various modes, has been growing steadily worldwide due to the influence of new technologies, global adoption of the Internet, and intensifying demand for a workforce trained periodically for the ever-evolving digital economy. Well-planned online learning experiences are meaningfully different from courses offered online in response to a crisis or disaster. Higher education institutions working to maintain instruction during the COVID-19 pandemic should understand those differences when evaluating emergency remote teaching (ERT). Online distance education involves more than just uploading educational content; instead, it is a learning process that provides learners with support, responsibility, flexibility, and choice. Henceforth, the research aimed to examine undergraduate students’ (n=238) perceptions about their preferred mode of learning during COVID-19. The paper identified a significant reluctance towards emergency remote teaching from first-year students. The paper also qualitatively investigated the underlying reasons through thematic analysis. The themed findings were (1) lack of social interactions, (2) difficulties staying engaged while studying from home, and (3) technological boundaries related to the students’ Internet connections in rural areas. The paper concludes with recommendations that aim to provide institutions and educations with practical guidance on how to tackle the outlined issues.